1997
DOI: 10.1103/physrevlett.78.2080
|View full text |Cite
|
Sign up to set email alerts
|

Collective Expansion in High Energy Heavy Ion Collisions

Abstract: Transverse mass spectra of pions, kaons, and protons from the symmetric heavy-ion collisions 200A GeV S 1 S and 158A GeV Pb 1 Pb, measured in the NA44 focusing spectrometer at CERN, are presented. The mass dependence of the slope parameters provides evidence of collective transverse flow from expansion of the system in heavy-ion induced central collisions. The purpose of studying ultrarelativistic heavy-ion collisions is to understand the nature of hadronic matter under extreme conditions. Specifically, we are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
115
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(128 citation statements)
references
References 33 publications
13
115
0
Order By: Relevance
“…The second analogy becomes evident in the transverse energy spectra of the collision products. Here it is found that heavier particles carry larger energies than the lighter ones [24]. Such a mass-dependence is interpreted as a result of "collective flow" (see e.g.…”
mentioning
confidence: 74%
“…The second analogy becomes evident in the transverse energy spectra of the collision products. Here it is found that heavier particles carry larger energies than the lighter ones [24]. Such a mass-dependence is interpreted as a result of "collective flow" (see e.g.…”
mentioning
confidence: 74%
“…Table IV of [2]. Dashed lines are drawn to guide the eye, corresponding to Equation (1) and also to earlier theoretical results for a single-component hadron gas in non-central heavy ion collisions as detailed in References [7,8]. Green symbols indicate our new result, based on our new exact solutions of fireball hydrodynamics for a collectively expanding and rotating, multi-component hadronic matter, as indicated by symbols with "MC theory" in the legends.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the NA44 Collaboration observed signals of collective expansion in symmetric heavy-ion collisions in 200 AGeV S+S and 158 AGeV Pb+Pb reactions at CERN SPS: the transverse mass spectra of pions, kaons and protons was found to be nearly exponential in these reactions, with a slope parameter that increased nearly linearly with the mass of the observed hadrons [1]. This linear mass dependence of the slope parameters was interpreted as an evidence of collective transverse flow in these heavy ion induced central collisions.…”
Section: Introductionmentioning
confidence: 99%
“…Such a solution of the equations of non-relativistic (NR) hydrodynamics is presented herewith. Physical realization of the solution is possible both by heavy ion collisions in the 30 MeV A -2 GeV A energy domain [3,4,5] and in a more limited sense by the NR transversal flows that seem to develop in high energy hadron-hadron and nucleus-nucleus collisions [1,6,7].…”
Section: Introductionmentioning
confidence: 99%